2022
DOI: 10.3389/fonc.2022.1047515
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of sarcopenia and systemic inflammation for patients with renal cell carcinoma following nephrectomy

Abstract: BackgroundTo clarify the prognostic effect of preoperative sarcopenia and systemic inflammation, and to develop a nomogram for predicting overall survival (OS) of patients with renal cell carcinoma (RCC) following partial or radical nephrectomy.MethodsPatients with RCC following nephrectomy from the First Affiliated Hospital of Soochow University during January 2018 to September 2020 were included in this study. The relationship between sarcopenia and inflammatory markers was identified by logistic regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…Previous research has evaluated the correlation between NLR and the risk of sarcopenia in different populations. For instance, a retrospective study involving 343 Chinese patients with renal cell carcinoma found an association between sarcopenia risk and NLR 18 , which was in line with the findings of Borges et al and Liu et al 29 , 30 . These studies suggested that a higher NLR might contribute to an elevated risk of sarcopenia in patients with hematological or solid cancers.…”
Section: Discussionsupporting
confidence: 84%
“…Previous research has evaluated the correlation between NLR and the risk of sarcopenia in different populations. For instance, a retrospective study involving 343 Chinese patients with renal cell carcinoma found an association between sarcopenia risk and NLR 18 , which was in line with the findings of Borges et al and Liu et al 29 , 30 . These studies suggested that a higher NLR might contribute to an elevated risk of sarcopenia in patients with hematological or solid cancers.…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, a recent meta-analysis found that patients with malignant neoplasms, including RCC and sarcopenia, had worse clinical outcomes than those who did not [ 28 ]. Interestingly, recent research has shown that preoperative sarcopenia and elevated systemic inflammatory markers, such as the modified Glasgow Prognostic Score including both CRP and albumin levels, were associated with a decreased survival [ 29 , 30 ]. Furthermore, a recent retrospective study found that patients with localized RCC who had both sarcopenia and hypoalbuminemia prior to surgery had a two-to-three-fold reduction in OS and recurrence-free survival after nephrectomy in an American population [ 22 ].…”
Section: Discussionmentioning
confidence: 99%